The Effect of Immersion Duration of Zoothamnium penaei Crude Protein Extracts to Stimulate Immune System in Litopenaeus vannamei Against Enterocytozoon hepatopenaei (EHP) - Anord Charles Nkuba; Gunanti Mahasri; Nunuk Dyah Retno Lastuti; Adamu Ayubu Mwendolwa (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The effect of immersion duration of shrimp to the immunostimulant from crude protein Zoothamnium penaei was determined. 20-minute immersion duration in crude protein from Zoothamnium penaei was found to increase the phagocytosis activities, phenoloxidase, and improve hepatopancreases of the shrimp. There is increase in phagocytosis activities, phenoloxidase and improved hepatopancreases cell within a three-week maintenance of shrimp with immersion after each seven days. There is interaction between immersion duration and maintenance time of shrimp into the crude protein from Zoothamnium penaei. Abstract Enterocytozoon hepatopenaei (EHP) is a spore-forming microsporidia intracellular parasite, which slough off the cells of the hepatopancreases of the shrimp. This study was intended to determine the effect of immersion duration and maintenance time to stimulate the immune system of shrimps by using a crude protein from Zoothamnium penaei to protect against EHP infections. The study used a completely randomized design where shrimps were divided into four groups each having five replicates. Groups P1, P2, P3 were immersed in immunostimulant for 10, 15, and 20 minutes respectively, except negative control. The phenoloxidase, phagocytosis activities, histopathology study were determined. Also, the molecular diagnosis of EHP was measured to confirm EHP infection in the shrimp samplesThe phenoloxidase activity significantly increased after immersion for 20 minutes (P3) from 0.64-, 0.72-, and 0.78-units min-1 mil -1 of protein on the first week, second week and third week, respectively. The phagocytosis activities of the sample immersed for 20 minutes were significantly increased to 68% on the second week. The sample also showed improved hepatopancreases epithelial cells with only 26% necrotic cell, less EHP spore and vacuolation. There was an interaction between immersion duration and maintenance time of the L. vannamei immersed in crude protein from Zoothamnium penaei. Twenty minutes immersion were significantly found to stimulate the immune system of the shrimp against EHP. The present work revealed that, the application of crude protein from Z. penaei is effective against EHP in shrimp culture.